Going international versus going global. The Case of the European Steel Pipe SMES - Elena-Mădălina VĂTĂMĂNESCU; Florina-Magdalena PÎNZARU; Andreia-Gabriela ANDREI; Vlad-Andrei ALEXANDRU (Revista de Management Comparat International)
In a world where competitiveness has become the second nature of the business environment, an insight on the organizations’ endeavour to go international seems natural. And yet, most of the times, under the lens of the worldwide researchers and practitioners, corporations have been settled as milestones. In this context, focusing on the small and medium enterprises (SMEs), on the managerial and entrepreneurial micro-universe may generate an alternative perspective on their approach on the international markets versus the global market. Starting from this premise, the paper intends to analyze the business internationalization versus business globalization perspectives assumed by managers of SMEs at present. The distinction between the two approaches is based on a step-bystep touch of the specialized markets versus a straight forward venture into far-away markets with a view to obtain higher profits. The emphasis was laid on 107 European steel pipe SMEs, whose managers responded to a 15-item questionnaire regarding their market strategies and experiences. As the results show, the socio-demographic characteristics of respondents have a considerable impact on their approaches on the issue, the choice for going international or going global relying on the subjects’ age, number of foreign partners, experience on the foreign markets and education field.